Antimicrobial Resistance or Delayed Appropriate Therapy—Does One Influence Outcomes More Than the Other Among Patients With Serious Infections Due to Carbapenem-Resistant Versus Carbapenem-Susceptible Enterobacteriaceae?. (23rd April 2019) - Lodise, Thomas P; Berger, Ariel; Altincatal, Arman; Wang, Rosa; Bhagnani, Tarun; Gillard, Patrick; Bonine, Nicole G
Abstract: Background: The relative contribution of antimicrobial resistance versus delayed appropriate treatment to the clinical and economic burden of Enterobacteriaceae infections is not well understood. Methods: Using a large US hospital database, we identified all admissions between July 2011 and September 2014 with evidence of serious Enterobacteriaceae infection. The "index date" was the earliest date on which a culture positive for Enterobacteriaceae was drawn. Infections were classified as carbapenem-resistant (CRE) or carbapenem-susceptible (CSE). Receipt of antimicrobials with activity against all index pathogens on the index date or ≤2 days thereafter was deemed as "timely"; all other instances were "delayed." Associations between CRE status and delayed appropriate therapy on outcomes were estimated using inverse probability weighting and multivariate regression models (ie, logistic model for discharge destination and composite mortality [in-hospital death or discharge to hospice] or generalized linear model for duration of antibiotic therapy, hospital length of stay [LOS], and costs). Results: A total of 50 069 patients met selection criteria; 514 patients (1.0%) had CRE. Overall, 67.5% of CSE patients (vs 44.6%, CRE) received timely appropriate therapy ( P < .01). Irrespective of CRE status, patients who received delayed appropriate therapy had longer durations of antibiotic therapy and LOS, higher costs, lower likelihood of discharge to home, and greater likelihood of the composite mortality outcome ( P for trend < .01). Conclusions: Delayed appropriate therapy is a more important driver of outcomes than CRE, although the 2 factors are somewhat synergistic. Better methods of early CRE identification may improve outcomes in this patient population. Abstract : Although resistance and delayed appropriate therapy both are associated with worse clinical and economic outcomes, delayed therapy appears to be the more important factor. As these 2 measures are correlated, earlier identification of CRE may improve outcomes.